Beating the market with small portfolios: Evidence from Brazil - André A.P. Santos (EconomiA, 2015)
Optimal portfolios with a restriction on the number of assets, also referred to as cardinality-constrained portfolios, have been receiving attention in the literature due to its popularity among market practitioners and retail investors. In most cases, however, the interest is in proposing efficient optimization methods to solve the problem, with little or no attention to the characteristics of the resulting portfolio such as risk-adjusted performance and turnover. We address this question by implementing a tractable reformulation of the cardinality-constrained version of the minimum variance portfolio. We analyze the out-of-sample performance of cardinality-constrained portfolios according to alternative criteria and check the robustness of the results for portfolios with alternative number of assets and under alternative re-balancing frequencies. Our empirical application for the Brazilian equities market shows that cardinality-constrained minimum variance portfolios with very few assets, e.g. 3 stocks, can deliver statistically lower portfolio risk and higher Sharpe ratios in comparison to the market index. Similar results are obtained for constrained portfolios with 5 and 10 assets and under daily, weekly, and monthly re-balancing frequencies. Our evidence indicates that it is possible to obtain better risk-adjusted performance with fewer securities in the portfolio by using an improved allocation scheme. – – Carteiras ótimas com restriç\~oes no número de ativos, também conhecidas como carteiras com restriç\~oes de cardinalidade, tem recebido grande atenç\~ao na literatura em funç\~ao da sua popularidade entre praticantes de mercado e pequenos investidores. Na maioria dos casos, entretanto, o interesse está em propor métodos eficientes de otimizaç\~ao para resolver o problema, com pouca ou nenhuma atenç\~ao às características das carteiras como desempenho ajustado ao risco ou turnover. Abordamos esta quest\~ao através da implementaç\~ao de uma reformulaç\~ao tratável do problema de minimizaç\~ao da variância da carteira sujeita à restriç\~ao de cardinalidade. Analisamos o desempenho fora-da-amostra das carteiras com restriç\~ao de cardinalidade segundo diversos critérios e checamos a robustez dos resultados para carteiras com diversos números de ativos e também diversas frequências de rebalanceamento. Nossa aplicaç\~ao empírica para o mercado acionário brasileiro mostra de carteiras de variância mínima com restriç\~oes de cardinalidade envolvendo um pequeno número de ativos, por exemplo, três aç\~oes podem obter níveis menores de risco e maiores índices de Sharpe em relaç\~ao ao índice de mercado. Resultados semelhantes s\~ao obtidos para carteiras restringidas com cinco e 10 ativos e com frequências de rebalanceamento diária, semanal e mensal. Nossa evidência indica que é possível obter um melhor desempenho ajustado ao risco com menos ativos na carteira através do uso de uma melhor estratégia de alocaç\~ao.
Keywords: G11; 330; Bootstrap; Cardinality constraint; Graduated non-convexity; Shrinkage estimator